2019
DOI: 10.2340/00015555-3121
|View full text |Cite
|
Sign up to set email alerts
|

Eye Complications During Dupilumab Treatment for Severe Atopic Dermatitis

Abstract: SIGNIFICANCE Dupilumab, the first biologic approved for treatment of atopic dermatitis, has demonstrated impressive clinical effect and quality of life-enhancing capacity in clinical trials. In these, dupilumab-associated conjunctivitis was reported in a minority of patients. We describe 10 patients treated with dupilumab where eye complications where common, suggesting the importance of close collaboration with an ophthalmologist. This is especially warranted among patients with severe, long-lasting atopic de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
75
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(84 citation statements)
references
References 13 publications
1
75
0
1
Order By: Relevance
“…Most of the reports suggested using hyaluronic acid eye drops, topical tacrolimus eye ointment, topical corticosteroid eye drops (e.g. fluorometholone, dexamethasone, hydrocortisone), artificial tears, compounded oily ciclosporin 1% eye drops, or antibiotic–topical corticosteroid combination therapies for the treatment of conjunctivitis during dupilumab treatment . Although one study found that antihistamine eye drops and artificial tears did not alleviate conjunctivitis, a small case series of 10 patients found that using artificial tears as a preventive method 1 week before starting dupilumab treatment may have reduced the incidence of conjunctivitis .…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Most of the reports suggested using hyaluronic acid eye drops, topical tacrolimus eye ointment, topical corticosteroid eye drops (e.g. fluorometholone, dexamethasone, hydrocortisone), artificial tears, compounded oily ciclosporin 1% eye drops, or antibiotic–topical corticosteroid combination therapies for the treatment of conjunctivitis during dupilumab treatment . Although one study found that antihistamine eye drops and artificial tears did not alleviate conjunctivitis, a small case series of 10 patients found that using artificial tears as a preventive method 1 week before starting dupilumab treatment may have reduced the incidence of conjunctivitis .…”
mentioning
confidence: 99%
“…fluorometholone, dexamethasone, hydrocortisone), artificial tears, compounded oily ciclosporin 1% eye drops, or antibiotic–topical corticosteroid combination therapies for the treatment of conjunctivitis during dupilumab treatment . Although one study found that antihistamine eye drops and artificial tears did not alleviate conjunctivitis, a small case series of 10 patients found that using artificial tears as a preventive method 1 week before starting dupilumab treatment may have reduced the incidence of conjunctivitis . Close collaboration with ophthalmologists for early and proper diagnosis and management of ocular complications in patients receiving dupilumab is also recommended …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, by avoiding direct application to the ocular surface the patient's eye may not be compromised by the combination of local administration of an immune modulating agent in combination with systemic blockade of IL‐4/IL‐13 pathways. This can theoretically impair viral defenses and expose the patient to potential infectious complications such as viral keratitis and uveitis (Ivert et al, ).…”
Section: Discussionmentioning
confidence: 99%